Self-medication with antibiotics among youths from Myanmar - Win, Pyae Sone; Win, Thida; Soe, Pa Pa (International Journal Of Community Medicine And Public Health, 2021)
Background: Self-medication with antibiotics becomes a public health concern in both developed and developing countries. It is a risk factor for antibiotic resistance, one of the biggest threats to global health, food security, and development today. The prevalence of self-medication with antibiotics varies across the countries, and such studies are still limited in Myanmar. Therefore, we aimed at describing the prevalence of and the factors facilitating self-medication with antibiotics in Myanmar. Methods: This cross-sectional study included face-to-face interviewing of 360 youths randomly selected from 6 townships of Mandalay city, Myanmar. Results: In this study, 36.67% of the youths self-medicated with antibiotics in the six months before the survey. The most common antibiotic used for self-medication was amoxicillin (70.94%). Runny nose (35.61%), cough (26.52%), and fever (25.76%) were the most typical symptoms for which antibiotics were taken. The main factor facilitating self-medication with antibiotics was easy accessibility (86.36%). One-third of youths selected antibiotics based on the advice of drugstore’s sellers. Most of the youths bought antibiotics at nearby drugstores. About two-thirds of youths stopped taking antibiotics after taking them one or two days, regardless of the outcome. Conclusions: The prevalence of self-medication with antibiotics was high among Myanmar youths. Law enforcement and regulations for inappropriate use of antibiotics is an urgent need to alleviate the consequences of self-medication with antibiotics. Awareness-raising and educational program targeting both drugstore owners and the public through various channels is necessary to reduce the inappropriate use of antibiotics.